Energy dilution with α-cellulose in diets for Atlantic cod (Gadus morhua L.) juveniles - effects on growth, feed intake, liver size and digestibility of nutrients - Lekva, Anette (The University of Bergen, 2009)
Atlantic cod (Gadus morhua) is known to grow large livers, especially farmed cod, but commercially, muscle growth is preferred, due to profits. Therefore, main focus in this feeding trial was to achieve lowered liver size, without compromising growth, feed utilization, digestibility of nutrients and elements, and maintain health. To accomplish this, indigestible fibre was used to dilute energy in feed. Atlantic cod were fed increasing α-cellulose inclusions (0, 6, 12 and 18%), in sustainable diets based on 50% plant ingredients (soy protein concentrate and wheat gluten) plus 50% fish meal as protein source (PP), or diets based on 100% fish meal as protein source (FM). The initial average cod live weight was 138 g, and the feeding trial lasted for 14 weeks. Good growth and feed utilization were obtained in all diet groups. At the end of the feeding trial growth was equal in all diet groups, but feed intake was higher for cod fed α-cellulose. The similar energy intake, even though dietary energy concentrations differed, and the dietary digestible macro nutrients (protein/fat/carbohydrates) and protein to energy (PE) showed similar ratios, indicate that the cod adjusted its feed intake in accordance to both energy and protein amount. The liver index (HSI) was not affected by increased α-cellulose. Digestibility of fat decreased with increased α-cellulose, in disagreement with increased lipid efficiency ratio (LER). Digestibility of protein was not affected by α-cellulose. Dry matter digestibility decreased with increased α-cellulose, in accordance with increased dry matter in faeces. There were variation in element concentrations between plant based and fish meal based diets. Some element digestibility results were negative, which might be due to presence of elements in water, although the diet is the main source of elements for fish. Most element digestibility results were not affected by increased α-cellulose. Though, Mn and Ba digestibility increased with increased α-cellulose, for cod fed PP diets, but not FM ...